Negotiations to implement area-based management tools beyond national jurisdiction: the scientific community’s view - Caldeira, Mariana; Teixeira, Heliana; Hilário, Ana (Frontiers in Marine Science, 2023)
A new international legally-binding instrument, under the United Nations Convention on the Law of the Seas (UNCLOS), for the conservation and sustainable use of marine biodiversity in areas beyond national jurisdiction has recently been agreed on– the BBNJ agreement. Area-based management tools (ABMTs), including marine protected areas (MPAs) have an important role in maintaining biodiversity and ecosystem services in the current context of multiple threats to the ocean and are one of central elements of new instrument. In this work, we assessed the perspective of the scientific community, throughout the period of negotiations, on the potential of the BBNJ treaty to promote the creation of new area-based management tools, including MPAs, and fulfil acknowledged gaps in ocean governance. A systematic literature review was conducted, resulting in 80 publications then analysed in detail. From these, a total of 608 key messages were retrieved and classified into: 1) Strengths (S), Weaknesses (W), Opportunities (O) or Threats (T) for a SWOT analysis and 2) one of six categories that cover crucial aspects for the successful implementation of the ABMTs in areas beyond national jurisdiction. A Sentiment Analysis (SA) to these key messages shows that the instrument has been perceived by the scientific community as an opportunity for conserving and achieving sustainable use of biodiversity. However, the scientific community also feels that agreement needs stronger provisions to ensure effective measures, which is reflected by the small number of identified strengths. An overall decrease in sentiment score over the negotiations period, i.e. a growing pessimism, was also observed, which is supported by an increase of weaknesses and threats identified in the final stages of the negotiations. Our results suggest that despite its potential to promote conservation in areas beyond national jurisdiction, the instrument should include a unified definition of MPA, address fishing activities and clarify conflicting terms in its provisions, such as the term “not undermine”. Further, we show that sentiment analysis is a useful tool to evaluate opinion trends and facilitate the integration of different and subjective perspectives into final provisions of complex social-political-environmental agreements, identifying positive and negative attitudes that can enable better solutions to address existing governance challenges in international waters.